Experiencing intercultural communication an introduction - Martin, Judith N.; Nakayama, Thomas K. (New York McGraw Hill, 2022)
"Recent events have highlighted, once again, the global interconnectedness of nations and people and underscored the need for intercultural communication knowledge and skills. For example, the worldwide spread of the COVID-19 virus disrupted the movement of people and goods and caused many countries to tighten their borders [the European Union "close[d] off a region encompassing at least 26 countries and more than 400 million people," and heightened intercultural tensions-as leaders of the two most powerful countries, China and the United States, traded insults and blamed each other for the social and economic devastation. We start with this focus on the Coronavirus as you may have been impacted by it. Your university or college may have moved classes online in the Spring of 2020 and you may know someone who has contracted it. Our cultures shape how we respond to these crisis situations. Do we follow the directives of the government officials? Or do we do what we want? Do we think about others? Or is it everyone for him/herself? After being asked to stay home and avoid contact with others, Katie Williams tweeted "I just went to a crowded Red Robin...It was delicious, and I took my sweet time eating my meal. Because this is America. And I'll do what I want."2 In contrast, South Koreans and Chinese tended to follow their governments' instructions, implemented by location tracking that measured and enforced stay-at-home directives. Do these cultural differences help explain why some countries experienced more fatalities and infections from the virus than others? As we work our way through this pandemic and the many more that will follow over the course of your lifetime, think about how cultural differences influence how different cultures respond to these crises. The virus has also accelerated call for reducing globalization. Although the United States has already withdrawn from some trade agreements and renegotiated others, the need for medical equipment intensified calls for more manufacturing in the U.S. What will happen to globalization? Will we move more toward closing borders or will we reach out and be more engaged with the world? Natural disasters may also affect intercultural communication. Climate change may bring about significant changes that require us to work with others around the world. Droughts, earthquakes, hurricanes, typhoons, tsunamis, and other natural disasters may increase the need for intercultural cooperation to help those in need. Social media presents other intercultural challenges. The 2020 video of another unarmed black man, George Floyd, killed by a white Minneapolis policeman went viral, leading to days of national and worldwide protests against racial inequality and some hope for change. On the other hand, social media have also been used to foment division and dissension. Thus, our use of social media can build bridges to other cultures or reinforce walls between them. How can we use our intercultural skills to help enrich our lives and the lives of those around us? As the world changes, how important is it for us to understand the past? Should we focus on culture-specific information? Or should we strive to develop more universal rules? How can anyone understand every culture around the world? Or every language? We wrote this book to shed light on these and many other questions about intercultural communication. As in our earlier books, we have tried to use information from a variety of approaches, drawing from social psychological approaches as well as from ethnographic studies and more recent critical media studies. However, the emphasis in this book is on the practical, experiential nature of intercultural communication. We still acknowledge that there are no easy answers to many intercultural situations. However, we attempt to give solid, practical guidelines, while noting the complexity of the task facing the student of intercultural communication. Stevis-Gredneff, M. & HYPERLINK "https://www.nytimes.com/by/richard-perez-pena" Pérez-Peña, R. (2020, March 17). Europe barricased borders to slow Coronavirus. (https://www.nytimes.com/2020/03/17/world/europe/EU-closes-borders-virus.html). White, M. D. (2020, March 15). Individualism doesn't justify endangering the lives of others. (https://www.psychologytoday.com/us/blog/maybe-its-just-me/202003 /individualism-doesnt-justify-endangering-the-lives-others)"--
Includes index
Keywords: Intercultural communication